Terminological analysis of terms «civil society» and «local community» - O. S. Kondratinskii (Aspekti Publìčnogo Upravlìnnâ, 2015)
The article discusses the concepts of civil society, local community. Considered and analyzed various scientific approaches to the interpretation of the term «civil society» and «local community» in the context of public administration reform and introduction of new approaches to the management of local development. According to the author, the basis for positive social and political change in the country should be at the level of civil society capable of newly incorporated local communities, as reviewed and analyzed various scientific approaches to the interpretation of the term «civil society» and «local community», in the context of democratic transformation of public administration in Ukraine. The more developed is civil society, the easier for citizens to defend their interests, the greater their possibilities of self-realization in various spheres of public life and the less danger of usurpation of power by its bodies or individuals. Defending material and spiritual independence of man from the state, ensuring legal guarantees of such independence protection of private and public interests of the people, civil society actively promotes the democratic process, during which a competent civil environment is formed. New approaches to generate an increase in business administration develop policies encouraging the involvement of civil society and business. However, the process of forming competent civil society at the local level remain little studied and require a thorough scientific analysis for intensive development of new mechanisms to influence the development of civil society.